A new approach for the treatment of subthreshold bipolar disorders: Targeted high dose levothyroxine and repetitive transcranial magnetic stimulation for mitochondrial treatment - Zamar, Andy; Lulsegged, Abbi; Kouimtsidis, Christos (Frontiers in Psychiatry, 2022)
Bipolar spectrum disorder includes subthreshold presentations. The condition is highly prevalent, disabling and associated with high mortality. Failure of diagnosis is high. Subthreshold presentations are generally less responsive to standard treatment and drug combinations are often needed. High Dose Levothyroxine has been reported to be safe and effective with this condition. Treatment response has been associated with mutations in thyroid activating enzymes and intra cerebral transporter protein carrier. Repetitive Transcranial Magnetic Stimulation (rTMS) has been proved to have neuroplastic effect. Present authors had reported clinical evidence of safe and effective use of a combination treatment protocol. Potential mechanisms of action of the combined treatment protocol and the role of mitochondria function are discussed.